Original position of the submarine below the Surface = -2 2/3= -8/3
Submarine at a depth of -2 2/3 feet descended by 5 1/2 feet.
So new position of the Submarine =
![(-8)/(3)-(11)/(2)\\\\ = \frac {-16 - 33}{2}\\\\ = (-49)/(6)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/ue10oqdlb627pcff5zcy86zon3hmcl919x.png)
To Reach the surface submarine must rise = 0-(-49/6)
As seen from the equation the two negative sign [(-)(-)] will change into a positive sign.
At the surface the position of the submarine = +49/6 feet